Analysis Of the Heavy Metal Cadmium (Cd) On the Quality of Liberica Coffee Seedlings (Coffea Liberica Bull Ex Hiern) Planted with Hyperaccumulator Mycorrhized Jarak Plant (Jatropha Curcas) - Huda, Nur; Maryani , Anis Tatik; Eliyanti; Pasla, Bambang Niko (Jurnal Prajaiswara, 2025)
Introduction/Main Objectives: Coffee in Indonesia is an important commodity, but excessive use of fertilizers and pesticides increases the levels of heavy metals, such as cadmium (Cd), in the soil, which is detrimental to plant quality and the environment. Phytoremediation with hyperaccumulator plants such as Jatropha can absorb cadmium and persist in contaminated soil. This study aims to study the interaction between mycorrhizal Jatropha plants (Jatropha curcas) and the growth of Liberica Tungkal Composite coffee seedlings (Coffea liberica Bull ex Hiern) on cadmium-contaminated land. Research MethodsThe study was conducted at the Teaching and Research Farm, Faculty of Agriculture, University of Jambi for 3 months (June - October 2024) using a Completely Randomized Design (CRD) with two treatment factors: factor C (C1 = 10 ppm, C2 = 20 ppm) and factor K (K0 = Coffee, K1 = Coffee + 1 Jatropha, K2 = 1 Coffee + 2 Jatropha, K3 = 2 Coffee + 1 Jatropha). Each combination was repeated 5 times, resulting in 40 treatments with a total of 120 plants. Data were analyzed using ANOVA and 5% BNT. Finding/Results: The results showed an interaction between cadmium treatment and coffee composition and distance on the variables of total leaf area and percentage of mycorrhizal infection.